2022
DOI: 10.3839/jabc.2022.012
|View full text |Cite
|
Sign up to set email alerts
|

Soil conditions during cultivation affect the total phenolic and flavonoid content of rosemary

Abstract: In this study, the effects of soil conditions on antioxidant activities of the aerial and underground parts of rosemary were assessed to determine the most effective soil conditions for cultivation. The antioxidant activity was the highest (51.58±2.93 µg/mL) when cultivated in the mixture of gardening soil and vermiculite using DPPH assay. The antioxidant activity of underground parts the highest (127.48±12.38 µg/mL) when cultivated in the mixture of soil, vermiculite, and perlite. ABTS assay showed that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…However, the bran extract maintained a survival rate above 90% at concentrations up to 200 µg/mL [21]. Another study that applied sorghum seed extract at 50, 100, and 200 µg/mL to RAW 264.7 cells found that treatment with 100 µg/mL of extract resulted in cell viability exceeding 89.28 ± 15.30%, indicating robust cell vitality across all tested seed extracts [22]. Our results showed a 70-80% cell survival rate at a lower concentration than those reported, which may be due to differences in the type of extraction solvent and extraction method.…”
Section: Toxicity Evaluation Of Raw 2647 Cells To Measure Anti-inflam...mentioning
confidence: 98%
“…However, the bran extract maintained a survival rate above 90% at concentrations up to 200 µg/mL [21]. Another study that applied sorghum seed extract at 50, 100, and 200 µg/mL to RAW 264.7 cells found that treatment with 100 µg/mL of extract resulted in cell viability exceeding 89.28 ± 15.30%, indicating robust cell vitality across all tested seed extracts [22]. Our results showed a 70-80% cell survival rate at a lower concentration than those reported, which may be due to differences in the type of extraction solvent and extraction method.…”
Section: Toxicity Evaluation Of Raw 2647 Cells To Measure Anti-inflam...mentioning
confidence: 98%